P5 2 Avian Affluence and Bovine Business Strategies - Rayson, Ben; Sharman, Mark; Knott, George; Molloy, David (Physics Special Topics, 2022)
In the story “Jack and the Beanstalk”, Jack obtains a golden egg from a goose owned by a giant. Using equations describing the curvature of avian eggs, the volume, mass and eventually the value of the egg were obtained. It was calculated that the egg had a value of £1775.69 in 1845 when the popular Henry Cole rendition was published, which could have purchased 332 cows. This is a profit of 33200%.